(untitled) (Politeja, 2020)
The Importance of Euroscepticism on the Political Scene of the Czech Republic. Conditions and Consequences Czech society is one of the most eurosceptic in the European Union. One of the reasons is a low degree of trust in authority (government, parliament) in general, also at the supranational level. Consequently, Czech political parties have eurosceptic slogans in their programs that do not prevent voters from supporting them, both in the elections to the Czech and European Parliaments. The political system is dominated by parties presenting the so‑ called „soft euroscepticism” (according to Taggart’s and Szczerbiak’s approach), such as: Action of Dissatisfied Citizens (ANO 2011), Civic Democratic Party (ODS) or Communist Party of Bohemia and Moravia (KSČM). In the 2017 election, they received a total of almost 50% of the vote. However, euroscepticism is not a threat to the Czech presence in the EU. Extremely eurosceptic parties do not enjoy great public support.